Effect of Some Surface Active Substances on the Spectrophotometric Determination of Th(IV) Using Some Coumarin Azo Dyes - El-Ansary, A.L.; Issa, Y.M.; Kandil, A.T.; Soliman, M.H. (Asian Journal of Chemistry, 2010)
The complexes of Th(lV) with some 8-(Arylazo)-6,7-dihydroxy-4-methylcoumarin are investigated spectrophotometrically. The optimumconditions for chelation, pH, sequence of addition, time, solvents andstoichiometry are critically evaluated. The studies reveal that 1 : 1 and1: 2 (M: L) complexes are formed. Beer's law is constructed for thespectrophotometric determination of Th(lV) in presence and absence ofsome surface active substances. The studies reveal that the use of surfactantsincreases the sensitivity of the methods of determination by raisingthe values of molar absorptivity (ε). The methods are precise as given bylow standard deviations ranging from 0.0097 to 0.0448 and high correlationcoefficient (r) ranging from 0.9884 to 0.9996. The values of molarabsorpitivity ε (LM-1 cm-1), specific absorpitivity a (mL g-1 cm-1) andSandell sensitivity S (μg cm-2) indicate the method to be quite sensitivecompared to standard method using Thoron. The tolerance of interferenceof foreign ions is investigated in the presence and absence of surfactants.The photometric titration methods using EDTA and F - as titrant are given.